An approach to analyse the factors behind the micromechanical response of 3D-printed composites. (1st April 2020) - Pascual-González, C.; Iragi, M.; Fernández, A.; Fernández-Blázquez, J.P.; Aretxabaleta, L.; Lopes, C.S.
Abstract: The state-of-the-art process for additive manufacturing of continuous-fibre reinforced polymers is fused filament fabrication (FFF), which has potential for reproducing robust and complex geometries. However, at the present, the mechanical performance of the resulting parts is affected by the low adhesion between layers and the high concentration of voids. This article proposes a characterisation approach to obtain describing factors for the contribution of composite constituents to the micromechanical behaviour of 3D printed composite materials. The methodology encompasses the examination of: (i) single fibre properties, (ii) fibre distribution and content and (iii) polymer nature. In doing so, this works attempts to standardise this methodology to obtain a more systematic and quantitative approach to this topic, promoting comparative research of additive manufacturing of commercially available continuous reinforced polymers. Although inhomogeneous fibre volume fractions observed in the microstructure may lead to trigger premature failure of the materials, calorimetric properties of polymer matrices might be the underlying factors of the relatively low mechanical response of additive manufactured composites. Taking into account manufacturing constrains, different strategies to enhance the mechanical performance of printed composites are proposed in the paper.